Effects of weight loss via high fat vs. low fat alternate day fasting diets on free fatty acid profiles - Varady, Krista A. (Sci Rep, 2015)
Cardiovascular disease risk is associated with excess body weight and elevated plasma free fatty acid (FFA) concentrations. This study examines how an alternate-day fasting (ADF) diet high (HF) or low (LF) in fat affects plasma FFA profiles in the context of weight loss, and changes in body composition and lipid profiles. After a 2-week weight maintenance period, 29 women (BMI 30–39.9 kg/m(2)) 25–65 years old were randomized to an 8-week ADF-HF (45% fat) diet or an ADF-LF (25% fat) diet with 25% energy intake on fast days and ad libitum intake on feed days. Body weight, BMI and waist circumference were assessed weekly and body composition was measured using dual x-ray absorptiometry (DXA). Total and individual FFA and plasma lipid concentrations were measured before and after weight loss. Body weight, BMI, fat mass, total cholesterol, LDL-C and triglyceride concentrations decreased (P < 0.05) in both groups. Total FFA concentrations also decreased (P < 0.001). In the ADF-LF group, decreases were found in several more FFAs than in the ADF-HF group. In the ADF-HF group, FFA concentrations were positively correlated with waist circumference. Depending on the macronutrient composition of a diet, weight loss with an ADF diet decreases FFA concentrations through potentially different mechanisms.